2016
DOI: 10.1097/meg.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Bowel Disease-Disability Index: validation of the Portuguese version according to the COSMIN checklist

Abstract: The Portuguese version of IBD-DI obtained is a reliable, valid, responsive, and interpretable (at the group level) tool to assess disability in Portuguese IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…With regard to the influence of sex, data were found that showed more disability in women than in men, with a difference of approximately six points. This finding is in line with the studies conducted in the French and Portuguese populations, which also observed worse IBDDI scores in women than in men [15,30]. It should be noted that the scoring system used was not the same in both studies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…With regard to the influence of sex, data were found that showed more disability in women than in men, with a difference of approximately six points. This finding is in line with the studies conducted in the French and Portuguese populations, which also observed worse IBDDI scores in women than in men [15,30]. It should be noted that the scoring system used was not the same in both studies.…”
Section: Discussionsupporting
confidence: 89%
“…The multivariate analysis in the fitted models also corroborated this finding. The literature reviewed supports this result, evidencing an association between disability and the situation of activity or inactivity in the disease [15,16,17,30,32]. Specifically, the systematic review mentioned above showed that patients with an active disease had higher rates of disability than those in remission, although it is again worth noting the high heterogeneity found among the studies reviewed [18].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, statistically significant influence was recorded for lower education in the UC and for operation and marital status in the CD group. Concerning activity, the relationship with disability is easily understandable and not surprising [36, 37]. But for the other parameters, we have not detected corresponding references in literature.…”
Section: Discussionmentioning
confidence: 86%
“…Patient-reported outcomes in combination with clinical-reported outcomes have been recently emphasized by medical organizations and regulatory agencies (i.e., FDA and EMA), becoming one of the primary aims of clinical trials focusing to evaluate novel molecules and treatment modalities for IBD patients experiencing disease relapse. In parallel, specific instruments, such as the IBD-DI, have been developed and validated in recent years [16, 17, 20, 22]. Based on these premises, our study was designed to evaluate clinical and pharmacological factors associated with impaired quality of life and disability in a large cohort of IBD patients consecutively enrolled at our IBD outpatient unit.…”
Section: Discussionmentioning
confidence: 99%